2020
DOI: 10.3390/antiox9101003
|View full text |Cite
|
Sign up to set email alerts
|

Allium subhirsutum L. as a Potential Source of Antioxidant and Anticancer Bioactive Molecules: HR-LCMS Phytochemical Profiling, In Vitro and In Vivo Pharmacological Study

Abstract: This study investigated Allium subhirsutum L. (AS) anticancer and antioxidant effects and inhibition of tumor angiogenesis in a murine model of skeletal metastases due to inoculation of Walker 256/B cells. Phytochemical composition of AS extract (ASE) was studied by High Resolution-Liquid Chromatography Mass Spectroscopy (HR-LCMS). Total phenolic and flavonoid contents (TPC and TFC) were determined. In vitro, the antioxidant properties were evaluated by reducing power and antiradical activity against DPPH. Can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
40
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 42 publications
(49 citation statements)
references
References 52 publications
3
40
0
Order By: Relevance
“…Over the years, medicinal plants have been used to develop a variety of formulations that combat injuries such as wounds, burns and cuts [ 15 ]. Several ethno-medicinal plants have been used for medicinal applications thanks to their wide biological activities and medicinal applications due to counteracting oxidative stress potential, lesser costs and high safety margins [ 16 , 17 , 18 ]. Plant extracts are known to exhibit many pharmacological properties (anti-hyperlipidemic, anti-proliferative, and immunomodulatory, etc.)…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Over the years, medicinal plants have been used to develop a variety of formulations that combat injuries such as wounds, burns and cuts [ 15 ]. Several ethno-medicinal plants have been used for medicinal applications thanks to their wide biological activities and medicinal applications due to counteracting oxidative stress potential, lesser costs and high safety margins [ 16 , 17 , 18 ]. Plant extracts are known to exhibit many pharmacological properties (anti-hyperlipidemic, anti-proliferative, and immunomodulatory, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…Plant extracts are known to exhibit many pharmacological properties (anti-hyperlipidemic, anti-proliferative, and immunomodulatory, etc.) through the multitude amounts of natural polyphenolic antioxidants [ 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Neither of the two drugs is a substrate of the p-glycoprotein. Cytochrome P450 (CYP) isoforms, such as CYP1A2, CYP2C19, CYP2C9, CYP2D6, and CYP3A4 are commonly used in biotransformation of drugs and xenobiotics [ 44 ]. In this study, the screened CYP enzyme isoforms data indicate that both CQ and HCQ were found to be inhibitors of only three isoenzymes, i.e., CYP1A2, CYP3A4, and CYP2D6 isoforms.…”
Section: Resultsmentioning
confidence: 99%